MULTI-OBJECTIVE OPTIMIZATION MODEL APPROACH FOR SUSTAINABLE MSME SUPPLY CHAINS: A BALANCE APPROACH BETWEEN ECONOMIC, ENVIRONMENTAL AND OPERATIONAL PERFORMANCE IN DEVELOPING COUNTRIES - Indra Welly Arifin; Hastuti Handayani Harahap; Frederick Rudy Sentosa Rajagukguk (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the influence of supply chain strategy on sustainable supply chain performance in Micro, Small, and Medium Enterprises (MSMEs), considering the role of operational efficiency and integration as intervening variables. The approach used is quantitative with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method using SmartPLS software. Data were obtained through distributing questionnaires to MSMEs in developing countries. The results of the study indicate that supply chain strategy does not have a significant direct effect on sustainable supply chain performance. However, supply chain strategy has a positive and significant effect on operational efficiency and integration, and operational efficiency and integration have a positive and significant effect on sustainable supply chain performance. In addition, the results of the mediation test indicate that operational efficiency and integration fully mediate the relationship between supply chain strategy and sustainable supply chain performance. The R-square value is in the moderate to strong category and the high Goodness of Fit value indicates that the research model has good predictive ability. These findings confirm that improving sustainable supply chain performance in MSMEs depends not only on strategy selection but also on the effectiveness of strategy implementation through increased operational efficiency and integration. This research provides theoretical contributions in the development of multi-objective optimization models as well as practical implications for MSMEs and policy makers in designing more efficient, integrated, and sustainable supply chain strategies.